"It's All About the Look": Making Sense of Appearance, Attractiveness, and Authenticity Online. (November 2022) - Foster, Jordan
Existing research on Instagram suggests that the mobile application is dominated by a cast of hegemonically attractive influencers. But calls for greater diversity and inclusion are on the rise, raising important questions about how social media influencers and the industry personnel who support them understand diversity and negotiate appearance ideals. Drawing on 40 interviews with influencers and industry personnel as well as a year of online observation, I find that hegemonic ideals surrounding appearance and attractiveness continue to shape who is (and isn't) perceived as worthy of visibility online. Industry personnel and influencers alike share that these ideals play an important role in cultivating a following on social media but remain convinced that change is underway. Emphasizing the importance of influencers' relatability and perceived authenticity, influencers, agents, and brand representatives shift focus away from broader issues surrounding the platform including the role that industry personnel play in moderating and constraining opportunities for diversity online.